ATP-binding cassette transmembrane transporters and their epigenetic control in cancer: an overview. (1st December 2016) - Arrigoni, Elena; Galimberti, Sara; Petrini, Mario; Danesi, Romano; Di Paolo, Antonello
ABSTRACT: Introduction : Members of the ATP-binding cassette (ABC) transmembrane transporters control the passage of several substrates across cell membranes, including drugs. This means that ABC transporters may exert a significant influence on the kinetics and dynamics of pharmacological agents, being responsible for the occurrence of multidrug-resistant (MDR) phenotype. Pharmacogenetic analyses have shed light on gene expression and polymorphisms as possible markers predictive of transporter activity. However, a non-negligible part of the variability in drug pharmacokinetics and pharmacodynamics still remains. Further research has demonstrated that different epigenetic mechanisms exert a coordinated control over ABC genes, and on the corresponding MDR phenotype. Areas covered : DNA methylation and histone modifications (namely acetylation, methylation, phosphorylation, etc.) significantly impact gene expression, as well as noncoding RNA molecules that are involved in the post-transcriptional control of the ABC transporters ABCB1, ABCC1 and ABCG2. We describe the epigenetic mechanisms of gene expression control for ABC transporters and their relevant association with the MDR phenotype in human cancer. Expert opinion : The clinical meaning of those observations is discussed in the review, highlighting the importance of the epigenetic control of the ABC transporters for the clinical therapeutic outcomes that despite their effects and applications, requires further investigation.